The morphofunctional and biochemical characteristics of opisthorchiasis-associated cholangiocarcinoma in a Syrian hamster model - G. A. Maksimova; M. Y. Pakharukova; E. V. Kashina; N. A. Zhukova; M. N. Lvova; M. V. Khvostov; D. S. Baev; A. V. Katokhin; T. G. Tolstikova; V. A. Mordvinov (Вавиловский журнал генетики и селекции)
The validity of experimental models of pathologies is one of the key challenges in translational medicine. Cholangiocarcinoma, or bile duct cancer, ranks second among oncological diseases of the liver. There is a strong association between bile duct cancer and parasitic infestation of the liver caused by trematodes in the family Opisthorchiidae. We have recently demonstrated that cholangiocarcinoma can develop in Syrian hamsters (Mesocricetus auratus) infected by Opisthorchis felineus and administered with dimethylnitrosamine. However, there is still no description of how this experimental model can possibly be used in translational research. The aim of this work was to study the morphological, functional and biochemical characteristics during cholangiocarcinoma development in Syrian hamsters infected by O. felineus and administered with dimethylnitrosamine. The experiment lasted 30 weeks with combined exposure to dimethylnitrosamine in drinking water at a dose of 12.5 ppm and a single injection of 50 metacercariae O. felineus. It was shown that the development of cholangiocarcinoma (18 weeks) increased the total number of basophils, eosinophils and monocytes, the relative number of granulocytes, the amount of total and direct bilirubin, and cholesterol and ALT levels, but reduced the relative number of lymphocytes. Based on pathological, morphometric and biochemical analyses, our model has characteristics similar to those in patients with opisthorchiasisassociated cholangiocarcinoma. Thus, this model can be used to test anticancer drugs, to study the mechanisms of cholangiocarcinogenesis and to search for molecular markers for early diagnosis of bile duct cancer.